NCMP-13. BRAIN MRI FINDINGS IN PATIENTS TREATED WITH CHIMERIC ANTIGEN RECEPTOR T-CELLS (CAR-T) DURING SEVERE NEUROTOXICITY. (11th November 2019) - Mokhtari, Sepideh; Arrington, John; Asquith, Justin; Bachmeier, Christina; Locke, Frederick; Lazaryan, Aleksandr
Abstract: INTRODUCTION: Severe neurotoxicity occurs in 30% of Diffuse Large B Cell Lymphoma (DLBCL) patients treated with CAR-T cell therapy. Brain MRI is used to assess and manage patients during neurotoxicity. Brain MRI can help understand which brain locations are affected during neurotoxicity. However, in majority of patients brain MRI is normal. It is unclear if the MRI findings are time dependent. Here we review our institutional experience with MRI findings. METHOD: We reviewed MRI brain of 38 patients who received CAR-T at Moffitt Cancer Center from October, 2017 to March, 2019. RESULTS: We identified 8 patients (21%) who had abnormal MRI findings. Five (63%) of these patients showed increased T2 FLAIR changes in bilateral mesial temporal lobes consistent with limbic encephalitis. One patient showed restricted diffusion and abnormal T2 FLAIR and T2 weighted images within the splenium of the corpus callosum plus increased T2 FLAIR changes in bilateral mesial temporal lobe, which resolved with follow up MRI in a month. One patient showed increased FLAIR signal intensity in left lateral cerebellum and cerebellar vermis. Two patients showed multiple new tiny areas of acute ischemic changes post CAR-T. One patient had several small and subtle areas of increased FLAIR signal intensity in bilateral frontal and parietal cortex on day 5 post CAR-T and multiple tiny areas of acute ischemia on day 10 post CAR-T. The median time to performing brain MRI was 8 days (range: 5–14). CONCLUSIONS: MRI can show T2 FLAIR changes consistent with limbic encephalitis mostly in temporal lobes but also in frontal, parietal lobes, and cerebellum. The MRI changes can happen anytime from day 5 to day 14 post CAR-T infusion. We need larger, controlled studies to have better understanding of MRI findings and whether they are time dependent in relation to when CAR-T was given.